Religious Humanism: Basic Education of Javanese Society - M. Agus Wahyudi; Maftukhin Maftukhin; Akhmad Rizqon Khamami (MKWK PAI Universitas Jambi, 2023)
Humanism is a Western philosophical thought that believes that humans have high values and positions and are at the center, or are referred to as anthropocentric. This kind of thinking has both positive and negative impacts. The positive impact is to prioritize human values, while the negative impact is that humans do not need God in their lives because they believe in their own efforts. Javanese people are known for their friendly, humanist and religious people. Religious humanism is a feature of the Javanese model of religious behavior. RMP. Sosrokartono is one of the figures from Java whose thoughts indirectly include human values that characterize the religious behavior of the Javanese people. The method in this research is a qualitative type. The data to be analyzed is in the form of primary data, namely the thoughts of RMP. Sosrokartono and secondary data, namely supporting data related to research. The aim of the research is to reveal the values religious humanism RMP. Sosrokartono and how it is implemented on the religious behavior of the Javanese people. The results of this study are that there are RMP. Sosrokartono whose name is ilmu kantong bolong, ilmu kantong, ilmu kantong kosong, and lmu sunyi in which there are values of religious humanism